ASPEK YURIDIS PEMBINAAN KHUSUS BAGI NARAPIDANA LANJUT USIA DAN PENYANDANG DISABILITAS PADA LEMBAGA PEMASYARAKATAN DI INDONESIA - Bernardus Pramawan (2019)
At present there are 4,408 prisoners and elderly prisoners scattered throughout Indonesia. The need for the presence of special rules regarding the standard of treatment for prisoners and elderly prisoners has been considered urgent as part of vulnerable groups The research method used is normative juridical approach to the legislation approach (statue aproach) Based on the data found, a number of conclusions can be summarized as follows: 1. Legal Regulations Against Older Prisoners and Persons with Disabilities in Correctional Institutions in Indonesia, namely Law Number 12 of 1995 concerning Corrections, Government Regulation of the Republic of Indonesia Number 32 of 1999 concerning Terms and Procedures for the Implementation of Correctional Assistance Rights, special arrangements for the standard of special treatment for elderly prisoners are more specifically found in the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 32 of 2018 concerning Treatment for Detainees and Elderly Prisoners and also for persons with disabilities. Law Number 8 of 2016 concerning Persons with Disabilities. Penitentiary systems are held in order to establish Correctional Guidance in order to become fully human, realizing mistakes in correcting themselves, and not repeating crimes so that they can be accepted again by the community, can actively play a role in development and live naturally as good and responsible citizens. 2. Provision of Accommodation for the Elderly and Persons with Disabilities in Receiving Guidance in Prisons, for elderly prisoners of the Minister of Law and Human Rights, have made international standards related to the treatment of prisoners and elderly prisoners, adjustments to the treatment of prisoners and elderly prisoners as referred to in regulations Permenkumham Number 32 Year 2018, which consists of protection, maintenance, improvement and recovery efforts is appealed through Circular Number PAS-03.0T.02.01 of 2019 concerning Handling of Prisoners / Elderly Prisoners so that the Ministerial Regulation must be guided by all correctional officers when dealing with elderly prisoners and detainees so that when they are placed in a state penitentiary / detention center their rights as an elderly group can still be fulfilled properly.